2012
DOI: 10.1111/j.1600-6143.2012.04033.x
|View full text |Cite
|
Sign up to set email alerts
|

The APOL1 Genotype of African American Kidney Transplant Recipients Does Not Impact 5-Year Allograft Survival

Abstract: APOL1 gene variants are associated with end-stage renal disease in African Americans. Here we investigate the impact of recipient APOL1 (apolipoprotein L-1) gene distributions on kidney allograft outcomes. We conducted a retrospective analysis of 119 African American kidney transplant recipients, and found that 58 (48.7%) carried two APOL1 kidney disease risk variants. Contrary to the association seen in native kidney disease, there is no difference in allograft survival at 5 years post-transplant for recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
141
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 15 publications
5
141
1
Order By: Relevance
“…On the other hand, the clear pathogenicity associated with the G1 and G2 disease alleles suggests that while wild-type APOL1 may promote cell survival, consistent with the long half-life of podocytes, these disease variants may have acquired a deleterious gain of function, which becomes manifest in combination with other genetic and/or environmental inputs. On the basis of kidney transplant studies, in which donor but not recipient APOL1 genotypes affected graft survival, 21,22 some would conclude that circulating APOL1 protein is less likely than intrinsic renal gene expression to be involved in the pathogenesis of APOL1-associated nephropathy. However, we caution against applying the transplant model to the pathogenesis of native kidney disease, in part because APOL1-associated kidney disease is a decades-long process whereas transplant failure is a short-term outcome confounded by many issues, including cold ischemia and use of nephrotoxic immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the clear pathogenicity associated with the G1 and G2 disease alleles suggests that while wild-type APOL1 may promote cell survival, consistent with the long half-life of podocytes, these disease variants may have acquired a deleterious gain of function, which becomes manifest in combination with other genetic and/or environmental inputs. On the basis of kidney transplant studies, in which donor but not recipient APOL1 genotypes affected graft survival, 21,22 some would conclude that circulating APOL1 protein is less likely than intrinsic renal gene expression to be involved in the pathogenesis of APOL1-associated nephropathy. However, we caution against applying the transplant model to the pathogenesis of native kidney disease, in part because APOL1-associated kidney disease is a decades-long process whereas transplant failure is a short-term outcome confounded by many issues, including cold ischemia and use of nephrotoxic immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the abundance of APOL1 in human serum and uptake of free APOL1 into podocytes in vitro ( 5 ), it was initially hypothesized that circulating APOL1 protein might contribute to APOL1 -associated nephropathy. Subsequent kidney transplantation studies failed to support this hypothesis (18)(19)(20); however, potential roles for circulating APOL1 protein in CVD and HDLcholesterol metabolism remain plausible ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a small study involving 119 African American kidney transplant recipients, Lee et al found no difference in graft survival in highrisk APOL1 (two alleles) compared to low-risk (zero or one allele) recipients (HR 0.96; 95% CI 0.61-1.49; p ¼ 0.84) (3). In a single center study from North Carolina, Reeves-Daniel et al examined outcomes from 106 African American deceased donors, of whom 22 (21%) had two APOL1 copies, and found that two APOL1 variants in a deceased donor was independently associated with a greater risk of graft failure (HR 3.84; p ¼ 0.0.84) (4).…”
mentioning
confidence: 98%